PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN DI KELAS XI IPA SMAN 12 PEKANBARU - Niffi Nedia Sari; Betty Holiwarni; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about implementation of learning model Learning Cycle 7E has been done with purpose to improve students critical thinking skills on the subject equilibrium solubility at the class XI science SMAN 12 Pekanbaru. Learning model Learning Cycle 7E is cycle model that involve student actively through the 7 phase in learning process that is elicit, engage, explore, explain, elaborate, evaluate and extend. This research was experimental research with pretest-postest design. The sample of this research were students of class XI IPA 5 as the experimental research and students of class XI IPA 4 as a control class that has been randomly selected after a test of normally and homogenity test. The technic of data analyze used is t-test to prove the truth of the hypothesis and N-Gain for category determination. Tabulation of data result obtained arithmetic-t bigger than table-t that is 8,64 bigger than 1,67; it’s mean there is an increase student’s critical thinking skills with implementation of learning model Learning Cycle 7E on the subject equilibrium solubility at the class XI science SMAN 12 Pekanbaru.N-Gain improves students critical thinking skills on the subject equilibrium solubility at the class XI science SMAN 12 Pekanbaru is 0,60 with medium category.Key Words: Learning Model Learning Cycle 7E, Critical Thinking Skills, Equilibrium Solubility